Effect of pore structure on methane adsorption characteristics in tectonically deformed coals - Wang, Peng; Ju, Yiwen; Ren, Chunhui; Li, Guofu; Xiao, Lei; Wang, Wei; Gao, Jian; Chen, Renzhe (Frontiers in Earth Science, 2025)
The regulation of pore structure on methane adsorption and free state in tectonically deformed coals directly affects the efficiency of coalbed methane extraction and coal mine safety. In this paper, we systematically characterised the full-size pore structure of different deformed coals (primary, brittle and ductile) in Huaibei mining area by integrating mercury intrusion, low-temperature nitrogen adsorption, carbon dioxide adsorption and methane isothermal adsorption, quantified the pore dynamics evolution law by combining with the fractal theory, and resolved the adsorption mechanism. The results show that: (1) the coal mainly consists of micropores (17.0–45.9%) and macropores (46.8–76.9%), with fewer mesopores (1.6–7.3%). With the intensification of tectonic deformation, the volume of micropores and macropores increased by 0.013 cm3/g and 0.097 cm3/g, respectively, and the specific surface area increased by ∼40 m2/g and <2 m2/g, respectively. Fractal analysis showed that macroporous complexity (D1) decreased while microporous complexity (D3) increased during ductile deformation; (2) microporous parameters (volume, specific surface area) dominated methane adsorption capacity (R2 > 0.7), while macroporous enlargement (up to 0.108 cm3/g) exacerbated the risk of free methane enrichment; (3) Brittle deformed coal is suitable for coalbed methane development due to microporous optimisation, while ductile deformed coal requires enhanced gas prevention and control due to free gas enrichment in large pores. The study reveals the dynamic correlation mechanism of ‘pore evolution, adsorption/free gas and disaster risk’ under the tectonic deformation gradient, which provides theoretical support for the efficient development and safe exploitation of coalbed methane.